Diretrizes para projetos de pontos de venda baseadas em sistemas de avaliação ambiental de varejo - Pozzatti, Gabriela Valente Caçola (Universidade do Vale do Rio dos Sinos, 2017)
The evolution of the world can be felt in many aspects of our day to day life. The way merchandise sales happen today has required architecture to accompany this transformation. This work deals with sustainability in retail outlets, and it was necessary to seek knowledge to understand the transformation that architecture has had over the years along with the forms of commerce. It was necessary to learn about the current situation in Brazil and the world in relation to sustainable commercial architecture and then to group concepts of sustainability and characteristics of a sustainable project. In addition, the paper seeks to identify the most used environmental assessment systems for retail and thus to analyze how the methodology, the applicability, the evaluated criteria and the way of scoring of them are employed. From this information collection, it was necessary to compare and analyze the different parameters used in the certification systems, seeking to understand those that have greater relevance and popularity. As a final result, it was possible to generate 35 sustainable guidelines divided into 5 groups: energy, user comfort, water, materials and maintenance. These guidelines help tenants to apply less environmentally harmful strategies at points of sale. A case study of two retail enterprises already certified in Brazil was carried out, and it was observed and compared how the guidelines proposed by the work behave in real projects. It was possible to notice that most of the directives proposed in the study were scored and helped the ventures analyzed to obtain their certifications. Thus it is realized that a lot of knowledge and responsibility is required to obtain a certification, but it was also possible to realize that many points are reached with small strategies during the design phase or even after the shop in operation. Finally, as a way of passing on to the shopkeepers the guidelines developed at work, a booklet was set up to be delivered at points of sale.
Keywords: Arquitetura; Sustentabilidade; Projeto; Varejo; Certificação ambiental; Architecture; Sustainability; Project; Retail; Environmental certification; ACCNPQ::Ciências Sociais Aplicadas::Arquitetura e Urbanismo